PENINGKATAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS MELALUI MEDIA WORD SEARCH DI SDN 066054 MEDAN DENAI - Siska Nurlianti; Syamsuyurnita; Silsia Risqha Revolina Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The subject of IPAS is learning about natural and social sciences where students can develop their knowledge about the concepts that have been given. In this case, the measure in determining the level of student success in understanding the concept is the learning results. Based on observations in the 4th grade of SDN 066065 Medan Denai, it was found that the lesson was taking the teacher who dominated the learning, and also didn’t use interactive learning media, which caused students to be passive in participating,so that the evaluation results of daily test scores weren’t optimal and had not reached the KKM of 70. The results show that out of 22 students, only 5 students have reached the KKM, while the other 17 students have not reached the KKM. It takes a learning model and media that can overcome this. The alternative is using Word Search media which aims to improve the learning results of grade IV students at SDN 066054 Medan Denai. This research uses qualitative and quantitative approaches with the type of class action research. The subjects were 22 students of 4th grade class at SDN 066054 Medan Denai. It is obtained that the observation of teacher and student activities has increased in each cycle, then student learning results have increased, There were 19 students who reached the KKM score with a classical completeness of 86.3%. So, it can be said that the use of Word Search media can improve student learning results at SDN 066054 Medan Denai.